Peculiarities of Practical Training of Childcare Workers at the Institutions of Higher Education in Ukraine - Glushok, Lyudmyla (Pedagogical Discourse, 2012)
The article deals with the problems of the childcare workers practical training and educators of the children of preschool age with additional specialization „Teacher of English in the kindergartens and primary schools” in particular (organizational and methodological bases, main tasks and guidance of the practical training). The significance of out-of-school activities is covered in the article.